Hypertension on Dialysis Patients: Influence Factor and Management - Swastika, Karina Dwi; Tarigan, Radar Radius (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Background: Hypertension remains prevalent and challenging to manage in patients with chronic kidney disease, even with renal replacement therapy. This phenomenon arises from a variety of components that contribute to and create an intricate process of interaction, which can impact the regulation of blood pressure in patients undergoing dialysis. The main goal of this overview is to find the influence factor of blood pressure in dialysis patients and investigate ways to better control their blood pressure by incorporating these factors.Methods: The literature searches using online databases such as PubMed and Google Scholar. Results: After doing an online search, we found 32 articles were relevant to this review topic. Discussion: There are additional elements that contribute to hypertension in dialysis patients, including excessive volume, heightened arterial rigidity, stimulation of the renin-angiotensin-aldosterone system, sleep apnea, activation of the sympathetic nervous system, and the administration of recombinant erythropoietin.Conclusion: Enhanced comprehension of the numerous variables at issue can effectively enhance blood pressure regulation in this group of individuals.